Pengaruh Desentralisasi Fiskal terhadap Pertumbuhan Ekonomi Provinsi-Provinsi di Indonesia, 2000-2012 - Parlaungan, KHALED TUANIDA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This thesis will determine the contribution of fiscal decentralization to regional economic growth with unit of analysis province in Indonesian from 2000-2012, as well as seeing the provincial typology based on economic growth and fiscal capacity index that divided in three periods. This thesis uses 9 economic variables both the fiscal and monetary, along with two dummy variables. The results in this thesis found that fiscal decentralization affect to province economic growth in Indonesia. However, there are still many who rely on the central provinces through the budget transfer. It can be seen from the number of provincial fiscal capacity index with low category.